CAPACITY RATING OF INTEGRATED CONE ROLLING-CONTACT BEARINGS OF 2K-V PLANETARY PIN-TOOTH GEAR - Sergey O. Kireyev; Boris N. Vasilyev (Advanced Engineering Research)
The estimation method for the basic dynamic radial bearing capacity, the dynamic equivalent radial load and the specified endurance of the integrated cone rolling-contact bearings of the 2K-V planetary pin-tooth gear with the off-centroid internal pin-tooth gear on the second stage is presented. These bearings are applicable in case where no standard cone rolling bearings can be used due to the dimensional specifications of the device.